Sudoku game and development of mathematical logical thinking - Arias Hidalgo, Elver Noel (2019)
Objective. To demonstrate the effect of sudoku game on the development of mathematical logical thinking in an Educational Institution of Huanuco. Methods. Research type was applied, with a quantitative approach, experimental level in its quasi-experimental variant, of two groups. Sessions with the use of sudoku in learning mathematical skills were applied to the experimental group, while the control group received mathematics classes using the traditional methodology. Hypothesis test was performed with the Z test. Results. After experimentation, logical mathematical thinking in its reasoning and problem-solving dimensions developed significantly. Data obtained showed that 61.1 % of students in the experimental group are in a regular level, and 25 % in a high level. Students in the control group, 91.7 % at a low level and 8.3 % at a regular level of students’ logical mathematical thinking. Conclusion. the application of the sudoku game has an effect on the development of mathematical logical thinking in students.